ANALISIS IDENTITAS KULTURAL DALAM PUISI “IBU INDONESIA” KARYA SUKMAWATI SOEKARNO PUTRI - Aryani, Elda; Yunengsih, Yuyu; Ismayani, Mekar (IKIP Siliwangi, 2019)
Every verse in poetry must have a specific purpose to convey to its readers, there is no temple that has no meaning and message to convey. This study aims to analyze cultural identity in the poem